First description of the complete mitochondrial genomes of the species Amblyomma humerale and Amblyomma geayi (Acari: Ixodidae), Amazon, Pará, Brazil - Lucas Henrique da Silva e Silva; Fábio Silva da Silva; Sandro Patroca da Silva; Paulo Henrique Gomes de Castro; Anita Roberta Stone; Leonardo Henrique Almeida Hernández; Daniel Damous Dias; Sâmia Luzia Sena da Silva; Lucia Aline Moura Reis; Hanna Carolina Farias Reis; Liliane Leal das Chagas; Tania Cristina Alves da Silveira da Cunha; et al. (Experimental and Applied Acarology, 2026)
The genus Amblyomma koch, 1844 contains approximately 138 species, which are mainly distributed in the Afrotropical, Oriental, Neotropical and Australasian zoogeographic regions. This is an important group of arthropod vectors responsible for transmitting a wide range of etiological agents that cause infections and diseases in humans and animals, and is therefore of great interest to public and veterinary health.This study describes and characterizes, for the first time, the complete mitochondrial genomes of the species Amblyomma humerale and Amblyomma geayi . The obtained sequences presented a circular molecule structured in 37 functional subunits with 13 Protein-Coding Genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNA (rRNAs), two replication control regions, and two regions called “Tick-box”. The phylogeny reconstructed using the maximum likelihood method, based on the 13 concatenated PCGs, produced a monophyletic group for the genus Amblyomma , including the investigated sequences. A. humerale and A. geayi were grouped into the clades formed by the subgenera Walkeriana and Anastosiella , respectively. By integrating complete sequences, the approach adopted expands the number of comparable characters, reduces biases associated with the use of isolated mitochondrial markers, and contributes to better statistical support for the recovered nodes, resulting in more stable and interpretable phylogenetic topologies. The data and information generated in this study can contribute to future taxonomic and evolutionary research on the genus Amblyomma .